The Relationship Academic Supervision and Achievement Motivation to the Teachers’ Performance at Elementary Schools - Edi, Firman; Sudadio, Sudadio (PPSDP International Journal of Education, 2023)
The aims of this research to find out the relationship academic supervising and achievement motivation to the teachers’ performance at the elementary schools in Tangerang Regency. In this research, there were 204 teachers in the population, and 146 teachers were selected as the sample using the proportional stratified random sampling technique. This is a correlation study aimed at investigating the relationship between academic supervision, motivation for achievement, and teachers’ performance, both individually and collectively. This research is highly valuable for school principals in advancing the field of educational management science, especially with regard to academic supervision and teacher performance development. The novelty in this study is that teacher performance has increased by optimizing the implementation of supervision and generating teacher achievement motivation. Achievement motivation so far has not been an aspect of coaching from school principals.